The Association of −330 Interleukin-2 Gene Polymorphism with Its Plasma Concentration in Iranian Multiple Sclerosis Patients - Arezou Sayad; Abolfazl Movafagh (Scientifica)
Multiple sclerosis (MS) is a chronic neuroinflammatory demyelinating disease of the central nervous system. The cytokine genes are involved in autoimmune diseases such as MS. In this study, we report the influence of −330 interleukin-2 (IL2) gene polymorphism on its plasma levels in a group of Iranian MS patients. In this study 100 MS patients and 100 ethnically, age, and sex matched healthy controls were selected from Medical Genetics Department of Sarem Women Hospital. Blood samples of all individuals were collected in EDTA tubes. The restriction fragment length polymorphism PCR (RFLP) method was applied to determine various alleles and genotypes in these individuals. Plasma concentration of IL2 was measured in all the samples using human IL2 kit. The frequency of −330 T/T IL2 genotype was higher in MS patients compared to normal individuals. Accordingly, the plasma levels of IL2 were significantly higher (P<0.0001) in patients when compared to the control group. In conclusion, in case of MS patients the −330 T/T IL2 genotype is associated with higher plasma levels of IL2.